2010
DOI: 10.1534/genetics.110.119594
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Adaptation: One or Many Waves of Advance of an Advantageous Allele?

Abstract: Models for detecting the effect of adaptation on population genomic diversity are often predicated on a single newly arisen mutation sweeping rapidly to fixation. However, a population can also adapt to a new environment by multiple mutations of similar phenotypic effect that arise in parallel, at the same locus or different loci. These mutations can each quickly reach intermediate frequency, preventing any single one from rapidly sweeping to fixation globally, leading to a ''soft'' sweep in the population. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
275
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(285 citation statements)
references
References 108 publications
(148 reference statements)
9
275
1
Order By: Relevance
“…This observation loosely fits with the parallel mutation model of Ralph & Coop [36] in which multiple adaptive haplotypes arise and spread in response to the same selective pressure. The geographical extent of the spread is perhaps associated with age of the mutation.…”
Section: Insights From Recent Genomic Studies Of Human Adaptive Evolusupporting
confidence: 79%
See 2 more Smart Citations
“…This observation loosely fits with the parallel mutation model of Ralph & Coop [36] in which multiple adaptive haplotypes arise and spread in response to the same selective pressure. The geographical extent of the spread is perhaps associated with age of the mutation.…”
Section: Insights From Recent Genomic Studies Of Human Adaptive Evolusupporting
confidence: 79%
“…In a recent paper, Ralph & Coop [36] explore the consequences of the speed at which an advantageous allele spreads for the genetic architecture of a trait. In particular, they consider cases in which adaptation to a novel selection pressure (such as a novel pathogen) might take place by 'multiple' mutations of similar phenotypic consequence that arise independently at the same locus or different loci (parallel mutations).…”
Section: Spatial Models Of Adaptive Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediterranean S alleles appear to descend from the African S alleles, many of them from the Benin haplotype (Flint et al, 1998). Recently, Ralph and Coop (2010) have shown that such parallel adaptation of multiple S alleles is not inconsistent with their theoretical spatial model and general estimates of mutation rate, gene flow, selection and population size, a finding consistent with that of Karasov et al (2010) who suggest that mutation does not limit adaptation in many situations. On the other hand, it has been proposed that a plausible explanation for much of the haplotype diversity around S alleles is that it reflects past recombination and gene conversion (Flint et al, 1998).…”
Section: Sickle Cell S or B S Or Hbsmentioning
confidence: 81%
“…The analogue of the stochastic partial differential equation (3) has no solution in dimensions two or higher and so the theory that we have appealed to above has no counterpart. Ralph and Coop (2010) examine the patterns of diversity resulting from competing selective sweeps arising through parallel adaptation. The randomness in their model is associated with the time and spatial location at which favoured alleles arise rather than genetic drift.…”
Section: Two Dimensionsmentioning
confidence: 99%